Unveiling Charge‐Transport Mechanisms in Electronic Devices Based on Defect‐Engineered MoS2 Covalent Networks. Issue 15 (3rd March 2023) - Ippolito, Stefano; Urban, Francesca; Zheng, Wenhao; Mazzarisi, Onofrio; Valentini, Cataldo; Kelly, Adam G.; Gali, Sai Manoj; Bonn, Mischa; Beljonne, David; Corberi, Federico; Coleman, Jonathan N.; Wang, Hai I.; et al.
Abstract: Device performance of solution‐processed 2D semiconductors in printed electronics has been limited so far by structural defects and high interflake junction resistance. Covalently interconnected networks of transition metal dichalcogenides potentially represent an efficient strategy to overcome both limitations simultaneously. Yet, the charge‐transport properties in such systems have not been systematically researched. Here, the charge‐transport mechanisms of printed devices based on covalent MoS2 networks are unveiled via multiscale analysis, comparing the effects of aromatic versus aliphatic dithiolated linkers. Temperature‐dependent electrical measurements reveal hopping as the dominant transport mechanism: aliphatic systems lead to 3D variable range hopping, unlike the nearest neighbor hopping observed for aromatic linkers. The novel analysis based on percolation theory attributes the superior performance of devices functionalized with π‐conjugated molecules to the improved interflake electronic connectivity and formation of additional percolation paths, as further corroborated by density functional calculations. Valuable guidelines for harnessing the charge‐transport properties in MoS2 devices based on covalent networks are provided. Abstract : Covalent networks of transition metal dichalcogenides (TMDs) represent an efficient strategy to reduce the interflake junction resistance in thin‐film devices. This multiscale investigation reveals that the molecular structure of the linker is crucial to control the overall charge‐transport mechanisms. This work highlights the great potential of defect engineering for the fabrication of high‐performance devices based on covalent TMD networks.